Development of Pesantren Nurul Haq Semurup: SWOT analysis - Noza Aflisia; Hendrianto Hendrianto; Nurwadjah Ahmad E.Q; Andewi Suhartini (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2022)
Abstract. This study aims to analyze the strengths, weaknesses, opportunities, and threats of Pesantren Nurul Haq Semurup. This is a qualitative research. The data sources come from the ustadz and santri of the Pesantren Nurul Haq Semurup, scientific articles and related written documents. Collecting data using observation, interviews, and documentation. To analyze the data, the researchers uses the stages of reducing data, presenting data, and verifying or concluding. The results show that the strength of the Pesantren Nurul Haq Semurup lies in the development of Islamic education, general science, life Skills, the strategic location of the pesantren, affordable education costs, and the attached pesantren label. The weaknesses include the fact that Arabic lessons do not have the right teachers, there are no special unique characteristics of the pesantren, they do not study the yellow book directly, and they do not have special standard books that students must master regarding tafaqquh fiddin. The high public interest in learning Islam and the independence of children are opportunities for pesantren to respond well. Meanwhile, the threat comes if it persists in a state where there is no dominant skill as a hallmark that students get after studying at this Pesantren.